Sexual Harassment, Law and Human Rights in Africa - Durojaye, Ebenezer; Nabaneh, Satang; Adebanjo, Toun. (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2023)
"The book is unique and somewhat first of its kind, providing extensive analysis on how sexual and gender- based violence affect marginalised communities..." --Dr Abiola Akiyode-Afolabi, University of Lagos & Executive Director, Women Advocate Research & Documentation Centre, Nigeria "This book takes an intersectional approach to human rights by exploring the intersection of gender, disability, refugee status, and social class, and in so doing, offers an invaluable contribution to the literature on women's human rights in Africa." --Prof Johanna Bond, Dean Faculty of Law Rutgers University, USA "It adopts a very unique-multidisciplinary perspective to sexual harassment by analysing it using the human rights based approach, something that has been lacking from the Global South!" --Dr Linet Sithole, Law Lecturer at Africa University, Zimbabwe This book delves into the endemic and pervasive issue of sexual harassment in Africa, examining it as a gendered expression of power and a gross violation of human rights. It explores sexual harassment in various sectors, including domestic work, academia, and the informal economy, across a range of African countries. The book also highlights the sexual harassment experienced by vulnerable populations, such as internally displaced people, people with disabilities, and women and girls traveling by air. With a keen focus on the intersection of law, feminism, and human rights, the book analyzes the role of the courts and national human rights institutions in addressing sexual harassment, drawing lessons from other jurisdictions. This book is a must-read for researchers, policymakers, and civil society organizations interested in gender power relations and women's rights in Africa and beyond. Ebenezer Durojaye is Professor and Head of the Socio-Economic Rights Project at the Dullah Omar Institute, University of the Western Cape, South Africa. Satang Nabaneh is Research Professor of Law at the University of Dayton School of Law and the Human Rights Center's Director of Programs. Adetoun Adebanjo is Legal Researcher and Consultant in Queensland, Australia.
1. Sexual harassment, human rights and feminism -- 2. Towards a woman-centered approach in addressing sexual harassment in Africa -- 3. Protecting women with disabilities from sexual harassment in africa -- 4. Nowhere is safe for women: adopting a rights-based approach in addressing in-flight sexual harassment -- 5. The dynamics of sexual harassment against women and access to protection for victims in zimbabwe's informal sector -- 6. Addressing the epidemic of sexual harassment in idp camps in Nigeria -- 7. Sexual harassment: vulnerability of domestic workers in Nigeria -- 8. The legal framework on sexual harassment in eswatini - a critical review in light of the maputo protocol -- 9. Sexual harassment in the workplace in the gambia: an analysis of recent developments from a feminist perspective -- 10. Sexual harassment in the university workplace: the place of section 35(5) of south africa's constitution -- 11. The role of the courts in addressing sexual harassment in Nigeria.
Keywords: International relations; Human rights; International Relations Theory; Politics and Human Rights